PENGARUH TEKANAN WAKTU, MATERIALITAS, RISIKO AUDIT, LOCUS OF CONTROL DAN TINDAKAN SUPERVISI TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT (Studi Empiris pada Kantor Akuntan Publik di DKI Jakarta) - Mariana Putri; Andreas Andreas; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effect of time pressure, materiality, audit risk, locus of control and supervision on premature sign off audit procedure at public accounting firms in Special Capital Region of Jakarta. The population of this research is 236 public accounting firms. Further, the sample method used was purposive sampling technique that obtained specific sample criterion which was only 41 internationally affiliated public accounting firms selected for this study. The data gathered in this study is the primary data which were collected through questioners. As much as 205 questioners spread to the participants, there were only 143 questioners returned completely. The data analysis technique in this study is multiple linear regression method using SPSS 20 statistics software. The result of the study proved that there is a significant relationship among time pressure, materiality, audit risk, locus of control and premature sign off audit procedure. Yet, there is no significant relationship between supervision and premature sign off audit procedure from the study finding. The coefficient of determination (R²) shows that jointly variables time pressure, materiality, audit risk, locus of control and supervision on the premature sign off audit procedure amounted to 71,10%.Keywords : time pressure, materiality, audit risk, locus of control, supervision, premature sign off